MENINGKATKAN PENGENALAN SAINS MENGGUNAKAN METODE KARYA WISATA PADA ANAK USIA 4-5 TAHUN DI PAUD AL-HIDAYAH KUBU RAYA - Selvianita, Selvianita; Purwanti, Purwanti; Ali, Muhamad (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe introduction of science has not been so applied, so that causing children to have less scientific ability, the purpose of this study is to improve the introduction of science using the method of tourism. The problem of this research is